2023
DOI: 10.3390/molecules28155821
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 and Arginase Inhibitory Activities of the Extracts from Some Members of Nelumbonaceae and Nymphaeaceae Families

Abstract: The objectives of this study were (1) to investigate the effect of extracts from some plants in the families Nelumbonaceae and Nymphaeaceae on phosphodiesterase 5 (PDE5) and arginase, which have been used in erectile dysfunction treatment, and (2) to isolate and identify the compounds responsible for such activities. The characterization and quantitative analysis of flavonoid constituents in the active extracts were performed by HPLC. Thirty-seven ethanolic extracts from different parts of plants in the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Moreover, the extract enhanced the effect of the NO donor but did not act itself as a direct sGC activator. Altogether, these results suggest that the phosphodiesterase inhibitory properties exhibited by the extract ( Panklai et al, 2023 ) may contribute to its relaxant effect, but the causal relationship has to be investigated in future studies. Regarding the effect of the extract on calcium fluxes, only extracellular calcium entry through ROCCs was weakly but significantly inhibited by the extract, without any effect on VOCC or intracellular calcium release from SR.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, the extract enhanced the effect of the NO donor but did not act itself as a direct sGC activator. Altogether, these results suggest that the phosphodiesterase inhibitory properties exhibited by the extract ( Panklai et al, 2023 ) may contribute to its relaxant effect, but the causal relationship has to be investigated in future studies. Regarding the effect of the extract on calcium fluxes, only extracellular calcium entry through ROCCs was weakly but significantly inhibited by the extract, without any effect on VOCC or intracellular calcium release from SR.…”
Section: Discussionmentioning
confidence: 93%
“…These data suggest that this compound is probably involved in the relaxant effect of the extract, but other compounds that remain to be identified are also involved. Of interest, our previous work demonstrated that the WL extract also contains, to a lesser extent, quercetin 3′-O-β-xylopyranoside, quercetin, 3-O-methylquercetin, kaempferol, and 3-O-methylkaempferol ( Panklai et al, 2023 ). Mechanistically, the main compound quercetin 3-methyl ether 3′-O- β -xylopyranoside shared with the extract the same effects on the NO-sGC-cGMP pathway and ROCCs but did not present an α 1 -receptor antagonistic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation